ANALISIS INTERAKSI DAN KONTRIBUSI SBIS JUALAH DENGAN PENYALURAN PEMBIAYAAN PERBANKAN SYARIAH - Nasution, Anriza Witi; Tambunan, Khairina; Ismal, Rifki; Batubara, Chuzaimah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
In Indonesia, the development of Islamic banking has increased significantly from year to year. Controlling the money supply through financing can be used with SBIS selling contracts as one of the sharia monetary policy instruments. The purpose of this research is to see how far the interaction and contribution of SBIS selling contracts with Islamic banking financing. The analytical method used is VECM. The results show that the causality between these two variables is not significant and for the interaction response both show stability in both the short and long term. This research recommends that SBIS is not only in the form of a ju'alah contract but also the implementation of the contracts given by the MUI.